Loperamide in Adult Acute Diarrhea - Shrestha, Ashish; Acharya, Samita (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: Decrease in duration of diarrhea significantly reduces morbidity, loss of working days, hospital bed occupancy and use of hospital resources. Loperamide is an established treatment of acute diarrhea to decrease the duration and frequency of unformed stool with only rare adverse reactions.Methods: This is a descriptive, cross sectional, parallel group, single centre study done in odd and even days of the month for treatment and control group. The study was conducted from 1st to 30th September 2010 in Patan Hospital Emergency Department.Results: Out of 104 patients, 43 patients were included in Loperamide group and 63 patients were taken in supportive treatment group. Mean duration of diarrhea was 16.3 and 41.9 hours in supportive plus Loperamide group and supportive treatment only group respectively. Mean difference in duration of diarrhea was 25.6 hours 95% CI (23.9 to 27.3) (P